Cultural heritage, violence and vaquejada (Revista do Tribunal Regional Federal da 3ª Região, 2022)
Cultural exclusion is one of the most important aspects in contemporary times for industrial societies. The application of the principle of non-violence against animals cannot disregard aspects of intangible cultural heritage, nor can it imply the criminalization of people for the way of living. The prohibition of vaquejada is a subject whose complexity serves to demonstrate the understanding of the Cultural Constitution in contrast to the biocentric paradigm. Methodologically, using theoretical references from constitutional theory, as well as from the analysis of judicial decisions of the higher courts, the cultural environment of vaquejada is analyzed as a problem space for issues that precipitate the backlash resulting from the friction between the anthropocentric and biocentric paradigm. In conclusion, the article aims to demonstrate that the objective of human relations without violence does not exclude the consideration of intangible cultural heritage as a characteristic landmark of pacification, the criminalization of which creates a true aspect of the criminal law's selectivity against individuals in the process of struggle for recognition.
Keywords: intangible cultural heritage; no violence; violence against animals; environmental protection; abolitionism